1997
DOI: 10.1046/j.1365-313x.1997.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis MALE STERILITY 2 protein shares similarity with reductases in elongation/condensation complexes

Abstract: The Arabidopsis thaliana MALE STERILITY 2 (MS2) gene product is involved in male gametogenesis. The first abnormalities in pollen development of ms2 mutants are seen at the stage in microsporogenesis when microspores are released from tetrads. Expression of the MS2 gene is observed in tapetum of wild-type flowers at, and shortly after, the release of microspores from tetrads. The MS2 promoter controls GUS expression at a comparable stage in the tapetum of transgenic tobacco containing an MS2 promoter-GUS fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
225
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(233 citation statements)
references
References 0 publications
8
225
0
Order By: Relevance
“…Notably, 13 genes including 4 genes classified as SP and 9 genes classified as NDP have expression levels of zero in the pollen transcriptome identified by Honys and Twell (2004). Except for AT2G47040 (VGD1), which was not detectable in Hony and Twell's experiment but was confirmed to be a pollen specific gene (Jiang et al 2005), the other 12 down regulated genes in Ms-cd1 flower buds including a reported tapetum specific gene MS2 (Aarts et al 1997) are most likely tapetum expressed or tapetum specific. To further clarify the association with fertility abortion in Ms-cd1, we compared expression patterns of these 12 genes with flower development expression data downloaded from Tair (http://www.arabidopsis.org) ( Table 3).…”
Section: Genes Preferentially Expressed In Anthersmentioning
confidence: 83%
See 1 more Smart Citation
“…Notably, 13 genes including 4 genes classified as SP and 9 genes classified as NDP have expression levels of zero in the pollen transcriptome identified by Honys and Twell (2004). Except for AT2G47040 (VGD1), which was not detectable in Hony and Twell's experiment but was confirmed to be a pollen specific gene (Jiang et al 2005), the other 12 down regulated genes in Ms-cd1 flower buds including a reported tapetum specific gene MS2 (Aarts et al 1997) are most likely tapetum expressed or tapetum specific. To further clarify the association with fertility abortion in Ms-cd1, we compared expression patterns of these 12 genes with flower development expression data downloaded from Tair (http://www.arabidopsis.org) ( Table 3).…”
Section: Genes Preferentially Expressed In Anthersmentioning
confidence: 83%
“…APG (At1g20130), which is suppressed 7.6 fold, is an antherspecific gene expressed during the period of microspore development in B. napus buds and flowers (Roberts et al 1993). MS2 (At3g11980), suppressed 5.8 fold, is expressed in tapetum of wild-type Arabidopsis flowers at, and shortly after, the release of microspores from tetrads (Aarts et al 1997). An ASK-beta gene (At3g61160) (Wellmer et al 2004) expressed in pollen and inside ovules was suppressed 3.9 fold.…”
Section: Verification Of Expression Pattern Using Rt-pcrmentioning
confidence: 99%
“…We identified 1,569 down-regulated genes and 848 upregulated genes (2,417 in total) with a change in expression of 2-fold or more in the tapetum and/or microspores at stages 8 and 9 between the wild type and ptc1 (Supplemental Data Set S1). Some genes previously identified as critical for postmeiotic anther development were down-regulated in the ptc1 microarray data (Table I), including a Cys protease (OsCP1; Lee et al, 2004), a fatty acyl-CoA reductase homologous to Arabidopsis MS2 (Aarts et al, 1997), lipid transfer proteins (Osc4, OsC6, YY1, and Os09g0525500; Tsuchiya et al, 1992;Hihara et al, 1996), a stilbene synthase (YY2; Hihara et al, 1996), BURP domain-containing proteins (RA8 and OsRAFTIN; Jeon et al, 1999), a P450 family member (CYP704B2; , a ribosomeinactivating protein (RA39; Jeon et al, 1999), and the putative homolog of AtMYB103 (Higginson et al, 2003;Zhang et al, 2007). Consistent with the RT-qPCR analysis, PTC1 showed up-regulation in the ptc1 mutant (2.97-fold at stage 8, 5.49-fold at stage 9), whereas genes involved in early tapetal and pollen regulation, such as CYP703A3 (Aya et al, 2009), TDR (Li et al, 2006), UDT1 (Jung et al, 2005), and GAMYB (Kaneko et al, 2004;Liu et al, 2010; Table I), showed no significant change.…”
Section: Ptc1 Is Preferentially Expressed In the Tapetum And Microspomentioning
confidence: 99%
“…As direct target genes of TDR, OsCP1 and OsC6, encoding a Cys proteinase and a lipid transfer protein (LTP), respectively (Lee et al, 2004;Zhang et al, 2010), are also directly or indirectly regulated by GAMYB and PTC1. Meanwhile, pollen exine-forming genes CYP704B2, CYP703A3, RAFTIN, and OsC6 (LTPs; Aarts et al, 1997;Wang et al, 2003;Aya et al, 2009;Liu et al, 2010;Zhang et al, 2010), involved in lipid metabolism and transport, are affected by GAMYB, PTC1, and TDR. Furthermore, TDR may act downstream of GAMYB (Liu et al, 2010).…”
Section: Ptc1 Determines a Conserved And Diversified Switch Of Apoptomentioning
confidence: 99%
“…Cj_ssh_male_t_017, which has sequence similarity with the Arabidopsis thaliana MS2 gene, was also isolated from this SSH library. The expression of the MS2 gene was observed in the tapetum of wild-type flowers at, and shortly after, the release of microspores from tetrads (Aarts et al 1997). The tapetal cells have a major role in pollen development by contributing to microspore release, nutrition, pollen wall synthesis, and pollencoat deposition (Bedinger 1992, Goldberg et al 1993.…”
Section: Discussionmentioning
confidence: 99%